EFEKTIVITAS PERHATIAN ORANG TUA DAN FASILITAS BELAJARTERHADAP PRESTASI BELAJAR SISWA KELAS TINGGISD MUHAMMADIYAH 15 SURAKARTATAHUN AJARAN 2016/2017 - Zulhijah, Kumala, Drs. Suwarno, S.H., M.Pd (2017)
The purpose of this research was to determine (1) The effectiveness of parental attention and learning facilities of student achievement of high class in SD Muhammadiyah 15 Surakarta year 2016/2017, (2) The effectiveness of parental attention of student achievement of high class in SD Muhammadiyah 15 Surakarta year 2016/2017, (3) The effectiveness of learning facilities of student achievement of high class in SD Muhammadiyah 15 Surakarta year 2016/2017. This research is quantitative research with survey research design. The results of the data analysis significance level of 5% was obtained: (1) Parental attention and learning facilities have significant efficacy of student achievement. This is based on test results of analysis of multiple linear regression equation Y = 38,309 + 0,226 X1 + 0,202 X2 wherein each regression coefficient of each variable is positive, with determination coefficient of 0,338 or 33,8%. (2) Parental attention have significant efficacy of student achievement. This is based on t test result is known that tcount > ttable, namely 2.514> 2.037 and the significance value < 0.05 is 0.017 < 0.05. While the relative contribution of 55% and the effective contribution of 18.59%. (3) learning facilities have significant efficacy of student achievement. This is based on t test result is known that tcount > ttable, namely 2.208> 2.037 and the significance value <0.05 is 0.035 <0.05. While the relative contribution of 45% and the effective contribution of 15.21%. It can be concluded that parental attention have greater effectiveness on student achievement of high class in SD Muhammadiyah 15 Surakarta year 2016/2017.